Countering transnational drug crime - Musaev Djamaliddin Kamalovich (Global Scientific Publishing, 2023)
Transnational drug crime is a kind of organized criminal activity, characterized by quantitative and qualitative indicators, carried out on the territory of several states, in order to obtain financial benefits from the commission of crimes in the field of drug trafficking, thereby representing one of the most serious global problems.
Keywords: transnational drug crime; counteraction; criminal law measures